Combined experimental and theoretical insight into the drug delivery of nanoporous metal–organic frameworks1. Issue 104 (11th November 2015) - Wang, Jiaping; Jin, Juncheng; Li, Fumei; Li, Baohong; Liu, Jianqiang; Jin, Jie; Wang, Chunfeng; Zeng, Yongping; Wang, Yukun
<x xml:space="preserve">Abstract</x> The comparison between calculated drug load values and some molecular level properties indicates the existence of a relationship between the void space of material and drug load capacity.